O ensino de História da África e da cultura afro-brasileira: uma proposta de ação decolonial em conexão com a didática da História - PINON, Alerrandson Afonso Melo (Universidade Federal do Pará, 2020)
The purpose of this work was to produce a methodology for teaching History with a decolonial orientation, with the aim of giving priority to teaching African history and Afro-Brazilian culture. We will demonstrate how decolonial thinking, with reference authors Aníbal Quijano, Walter Mignolo and Catherine Walsh, can reveal to us how the history of Africa and Afro-Brazilian culture have historically been subordinated in school curriculum. We will also emphasize the main criticisms of Eurocentrism in the production of historical knowledge, arising from post-colonial African thought, having Mudimbe, Mbembe and Appiah as reference authors. From these reflections, it was possible to draw the guidelines that guided the formulation of the pedagogical intervention work in the school space. In order to carry out the intervention work, research was carried out on the historiographic collection available in the libraries of the researched school spaces, in addition to research on the historical meanings that students attributed to the History of Africa and the relations of the African continent with Brazil, before and after intervention work. In order to understand the historical meanings attributed by students to Africa and their relations with Brazil, a dialogue was carried out with the Didactics of History, having historian Jörn Rüsen and his concepts of historical consciousness and historical culture as the author of reference. The connection with the Didactics of History allowed diagnoses about how students historically think about the History of Africa and its relations with Brazil. Based on this diagnosis, it was possible to formulate intervention work in the school space, where I developed educational products (didactic texts and slide shows) on the history of Africa and Afro-Brazilian culture that were used in my teaching practice in two schools of basic education in the metropolitan region of Belém do Pará: Helder Fialho Dias (SEMEC Belém) and Américo Souza de Oliveira (SEDUC Pará). The intervention took place in the second half of 2019 and was carried out from expository classes and evaluative activities that culminated in Cultural Shows and seminars presented by the students. After the intervention, a research was carried out to evaluate the learning results, in which was possible to diagnose significant learnings, which led the students: to overcome the reductionism from the History of Africa to the History of slavery; to undo negative images and break the stereotypes created about the History of Africa and the African continent; and to overcome racism.